Valuing the Swahili Cultural Heritage: A Maritime Cultural Ecosystem Services Study from Kilwa, Tanzania. (4th July 2019) - Ichumbaki, Elgidius B.; Pollard, Edward
ABSTRACT: During the second millennium CE, the medieval settlements of Kilwa in southeastern Tanzania were part of the Indian Ocean trading system that left a clear physical legacy of stone towns along with oral histories and sailing traditions. Modern developmental activities including exploration of oil and gas, house building, and establishment of tourism infrastructures have led to the reuse of heritage site, hence, an inevitable pressure upon heritage preservation. Unfortunately, despite being outdated and very colonial, legislations enacted to support protection of heritage sites are inadequately enforced. This paper looks at complementary conservation challenges by considering the value of medieval monuments and intangible heritage assets within the ecosystem services. We also provide some suggestions on how exploitation of non-material benefits in the form of Cultural Ecosystem Services from legends based on intertidal limestone features resembling boats and giants, as well as the venerated baobabs and mangroves can become sustainable.